FROM CLANS TO CORPORATIONS: UNDERSTANDING THE DRIVERS OF CADRE TRAJECTORIES IN KAZAKHSTAN - Issenova, Malika (Nazarbayev University School of Sciences and Humanities, 2025)
This thesis investigates the logic of cadre trajectories in Kazakhstan under the presidency of Kassym-Jomart Tokayev, with a particular focus on ministerial appointments from 2019 to 2025. Using a mixed-methods approach that combines quantitative analysis of a custom-built dataset with qualitative content analysis of open-access sources, this study evaluates two predominant explanations for elite circulation: clan-based affiliations and ties to financial-industrial groups (FIGs). As such, it argues that while both frameworks offer valuable insights, the findings indicate that neither of them fully explains the logic of cadre trajectories under President Tokayev. Instead, the present study asserts that the trajectories of ministers are contingent upon the nature and function of the specific ministries they lead. Hence, it has been shown that ministries associated with economic rent or high visibility, such as Energy, National Economy, or Labor and Social Protection, tend to have higher turnover and are often linked to elite bargaining or performance-related dismissals. Conversely, ministries like Defense, Emergency Situations, or Justice, which are typically seen as integral to regime stability and security, exhibit greater continuity, as well as less public visibility. As such, this thesis argues that cadre trajectories under President Tokayev are largely sector-specific, hence they reflect a differentiated governance logic rooted in institutional purpose rather than a uniform pattern of elite or clan affiliation.
Keywords: political elites; cadre trajectories; cadre rotation; kazakhstan; governance; Type of access: Embargo